2017
DOI: 10.1177/1358863x16689831
|View full text |Cite
|
Sign up to set email alerts
|

Non-compressible ABIs are associated with an increased risk of major amputation and major adverse cardiovascular events in patients with critical limb ischemia

Abstract: Ankle-brachial indices (ABIs) are important for the assessment of disease burden among patients with peripheral artery disease. Although low values have been associated with adverse clinical outcomes, the association between non-compressible ABI (ncABI) and clinical outcome has not been evaluated among patients with critical limb ischemia (CLI). The present study sought to compare the clinical characteristics, angiographic findings and clinical outcomes of those with compressible (cABI) and ncABI among patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In prior studies, for the subset of patients with PCA and CLI, there was angiographic evidence of extensive disease with long lesions and small vessel diameters. 40 , 41 Accordingly, our hypothesis is that the mechanism for increased risk for amputation in patients with PCA was likely due to presence of a combination of the following factors: underrecognition of CLI, extensive atherosclerotic disease with long lesions, and small vessel diameter more likely to occur in patients with diabetes and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In prior studies, for the subset of patients with PCA and CLI, there was angiographic evidence of extensive disease with long lesions and small vessel diameters. 40 , 41 Accordingly, our hypothesis is that the mechanism for increased risk for amputation in patients with PCA was likely due to presence of a combination of the following factors: underrecognition of CLI, extensive atherosclerotic disease with long lesions, and small vessel diameter more likely to occur in patients with diabetes and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have shown that patients with PCA were more likely to have diabetes, to have chronic kidney disease, and to undergo limb amputation. 40 , 41 Weinberg et al 42 have shown by angiography that patients with PCA have high rates of PAD with predilection for the infrapopliteal arteries. In prior studies, for the subset of patients with PCA and CLI, there was angiographic evidence of extensive disease with long lesions and small vessel diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these patients should be considered as likely to have PAD and always sent for further examination (bear in mind that we are discussing a screening test now, not a diagnostic test). Such a decision is also supported by the conclusions of Aboyans 7 and others 8,9 that high ABI bears a significant risk of development of serious complications and should be considered as PADequivalent 7 .…”
Section: Discussionmentioning
confidence: 84%
“…ABI values of 0.91 to 0.99 are considered "borderline" while values over 1.40 indicate non-compressible arteries [4][5][6] associated with vascular calcifications, potentially bearing an even more serious effect on the quality of life than low ABI (ref. [7][8][9] ). The guidelines recommend use of the higher SBP from the two arteries at the ankle level for ABI calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, among 284 patients with CLI, the presence of noncompressible vessels was associated with a greater likelihood of amputation (hazard ratio, 1.75 [95% CI, 1.12-2.78]) and major adverse cardiovascular events (hazard ratio, 2.04 [95% CI, 1.35-3.03]) over 3 years of follow-up than in those with CLI and compressible vessels. 20 It is noteworthy that the ABI may be partially compressible, with resultant values that underestimate the severity of disease; in a series of 5984 patients with CLI who were undergoing revascularization in a large statewide registry, 21% had normal ABI and 53% had only mildly reduced ABI. 13 Infrapopliteal PAD is present among a large proportion of patients presenting with CLI.…”
Section: Limitations Of Abi and Ankle Systolic Pressurementioning
confidence: 99%